Molecular Wormhole Chemistry: Electronic Non-Locality Induced by Wormhole-Like Geometries in Conjugated Molecular Systems - Barack Ndenga (Publisher, 2025)
In this work, I present the concept of molecular wormhole chemistry, a new theoretical framework where electronic non-locality emerges in conjugated molecular systems due to geometries analogous to spacetime wormholes. By combining the tight-binding Hamiltonian with Green’s function formalism, I derive equations that describe how electrons may bypass conventional geometric pathways and instead follow topological shortcuts. I also introduce a new index that quantifies wormhole-induced non-locality in molecular systems. This approach offers a rigorous mathematical resolution to the question of how geometry and topology can control quantum behavior in molecules. I argue that conjugated π-systems are capable of hosting such wormhole-like connections, opening a new direction in quantum chemistry and topological molecular design.
This work presents a complete resolution on the chemistry of molecular wormholes, introducing new mathematical formulations, rigorous proofs, and conceptual frameworks that bridge quantum chemistry, topology, and electronic non-locality. The manuscript includes advanced theoretical developments, scientifically verified demonstrations, and conceptual figures that illustrate the principles of intramolecular wormholes. The study highlights how molecular topology and quantum tunneling effects can be understood through a wormhole-inspired framework, opening novel perspectives for molecular electronics, quantum coherence, and nanoscale transport phenomena. This research has been prepared in international scientific English and is intended for global publication and peer review.